Phytoplankton spring bloom initiation: The impact of atmospheric forcing and light in the temperate North Atlantic Ocean. (November 2019) - Rumyantseva, Anna; Henson, Stephanie; Martin, Adrian; Thompson, Andrew F.; Damerell, Gillian M.; Kaiser, Jan; Heywood, Karen J.
Highlights: Unique 8 month glider dataset used to investigate phytoplankton bloom initiation. 3 hypotheses for the mechanism of spring bloom initiation are examined. Results are consistent with critical depth hypothesis if mixing depth is considered. Abstract: The spring bloom dominates the annual cycle of phytoplankton abundance in large regions of the world oceans. The mechanisms that trigger blooms have been studied for decades, but are still keenly debated, due in part to a lack of data on phytoplankton stocks in winter and early spring. Now however autonomous underwater gliders can provide high-resolution sampling of the upper ocean over inter-seasonal timescales and advance our understanding of spring blooms. In this study, we analyze bio-optical and physical observations collected by gliders at the Porcupine Abyssal Plain observatory site to investigate the impact of atmospheric forcing and light conditions on phytoplankton blooms in the temperate North Atlantic. We contrast three hypotheses for the mechanism of bloom initiation: the critical depth, critical turbulence, and dilution-recoupling hypotheses. Bloom initiation at our study site corresponded to an improvement in growth conditions for phytoplankton (increasing light, decreasing mixing layer depth) and was most consistent with the critical depth hypothesis, with the proviso that mixing depth (rather than mixed layer depth) was considered. After initiation, the observed bloom developed slowly: over several months both depth-integrated inventories and surface concentrations of chlorophyll a increased only by a factor of 2 and 3 respectively. We find that periods of convective mixing and high winds in winter and spring can substantially decrease (up to an order of magnitude) light-dependent mean specific growth rate for phytoplankton and prevent the development of rapid, high-magnitude blooms.